Gendered experiences of leading and managing through COVID-19: patriarchy and precarity. Issue 7 (21st October 2020) - Mavin, Sharon; Yusupova, Marina
Abstract : Purpose: The purpose of this paper is to highlight key issues for women managers, leaders and precarious academic women during COVID-19 in organisations and in academy. Design/methodology/approach: This paper shares the authors' personal experiences during COVID-19 in the UK as a woman Professor and Director of a Business School and a woman Research Associate and link these with existing scholarship to reflect on areas for continued research and action. Findings: This paper underlines how COVID-19 destabilises the progress made towards gender equality. Practical implications: This paper outlines future avenues for research and practice as a result of experiences of COVID-19. Originality/value: This paper looks at the gendered implications of COVID-19 for women across organisational hierarchies and highlights commonalities in their experiences and devastating effects of the pandemic.